2006
DOI: 10.1111/j.1365-3091.2006.00771.x
|View full text |Cite
|
Sign up to set email alerts
|

The orientation of helical flow in curved channels

Abstract: The planform patterns of meandering submarine channels and subaerial fluvial bends show many similarities that have given rise to strong analogies concerning the fluid dynamics of these channel types. Existing models of helical motion in open-channel bends depict flow that is characterized by surface flow towards the outer bank, and basal flow towards the inner bank. This paper investigates and compares, through an analytical model and physical experiment, flows within fluvial meanders, and submarine channel b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
195
2
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(229 citation statements)
references
References 48 publications
29
195
2
3
Order By: Relevance
“…4 Kneller, 2009;Pyles et al, 2012), direct measurement of density flows in modern sinuous submarine channels and similar downslope analogs (e.g., Vangriesheim et al, 2009;Parsons et al, 2010;Sumner et al, 2014), physical experiments (e.g., Corney et al, 2006;Keevil et al, 2006;Peakall et al, 2007;Wells, 2010, 2013;Ezz et al, 2013;Janocko et al, 2013;Cossu et al, 2015), and numerical simulations (e.g., Corney et al, 2006;Imran et al, 2007;Giorgio Serchi et al, 2011;Dorrell et al, 2013;Janocko et al, 2013;. However, whilst there is a good understanding of the underlying flow processes in contourite channels (e.g., Faugères et al, 1993;Rebesco, 2005;Faugères and Stow, 2008;Rebesco et al, 2014), the detailed three-dimensional flow dynamics and their control on sedimentation in isobath-parallel contourite channels remain comparatively poorly studied.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Kneller, 2009;Pyles et al, 2012), direct measurement of density flows in modern sinuous submarine channels and similar downslope analogs (e.g., Vangriesheim et al, 2009;Parsons et al, 2010;Sumner et al, 2014), physical experiments (e.g., Corney et al, 2006;Keevil et al, 2006;Peakall et al, 2007;Wells, 2010, 2013;Ezz et al, 2013;Janocko et al, 2013;Cossu et al, 2015), and numerical simulations (e.g., Corney et al, 2006;Imran et al, 2007;Giorgio Serchi et al, 2011;Dorrell et al, 2013;Janocko et al, 2013;. However, whilst there is a good understanding of the underlying flow processes in contourite channels (e.g., Faugères et al, 1993;Rebesco, 2005;Faugères and Stow, 2008;Rebesco et al, 2014), the detailed three-dimensional flow dynamics and their control on sedimentation in isobath-parallel contourite channels remain comparatively poorly studied.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Ekman boundary layers will be directed to the left (looking 14B, 14 C, and 15B). They show a vertical structure as governed by the vertical velocity profile (Corney et al, 2006(Corney et al, , 2008Dorrell et al, 2013;Peakall and Sumner, 2015), with low density stratification induced by the likely presence of fine-grained sediment, leading to the vertical position of the downstream velocity (U max ) being…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiment of Corney et al [2006] and Keevil et al [2006] involved flow that was rather deep with a flow thickness to width ratio of 0.71 and flow thickness to centerline radius of curvature ratio of 0.47. Imran et al [2008] showed that the analytical model utilized by Corney et al [2006] predicts the maximum radial velocity to be more than twice the maximum tangential velocity when the levee height of their experimental channel is used as the scale for flow depth as done by Corney et al [2006].…”
Section: Introductionmentioning
confidence: 99%
“…[6] Recently, Corney et al [2006] conducted small scale laboratory experiments on saline density flow in a curved channel with multiple bends. They measured the velocity field at the apex of a channel bend using an array of unidirectional Ultrasonic Doppler Velocity Probes (UDVP).…”
Section: Introductionmentioning
confidence: 99%